Sex in Australia: Autoerotic, esoteric and other sexual practices engaged in by a representative sample of adults - Juliet Richters; Andrew E. Grulich; Richard O. deVisser; Anthony M.A. Smith; Chris E. Rissel (Elsevier, 2003)
Abstract Objectives : To describe the prevalence of a range of autoerotic and other non‐coital sexual practices among Australians. Method Computer‐assisted telephone interviews were completed by a representative sample of 10,173 men and 9,134 women aged 16-59 years (response rate 73.1%). Respondents were asked whether in the past year they had: masturbated, engaged in various other autoerotic activities, or engaged in any of six other non‐coital or esoteric practices. Results : Half of the respondents (65% men, 35% women) had masturbated in the past year. Nearly half (48%) of the men and 25% of the women had masturbated in the past four weeks, among whom men had done so a mean of 5.8 times and women 3.3 times. About a quarter of all respondents had watched an X‐rated film (37% men, 16% women), 12% of men and 14% of women had used a sex toy, and 17% of men and 2% of women had visited an Internet sex site. 17% of men and 14% of women had engaged in digital‐anal stimulation with a partner. Phone sex, role play or dressing up, bondage and discipline, sadomasochism or dominance and submission (BDSM‐DS), fisting (rectal or vaginal, insertive or receptive) and rimming (oral‐anal stimulation) were all engaged in by less than 5% of the sample. Conclusion Most of the practices studied were engaged in by more men than women. A range of autoerotic activities are both substitutes for partnered sex and additional sources of pleasure for people with sexual partners.